Identification of Campylobacter jejuni on the basis of a species-specific gene that encodes a membrane protein. - Stucki, U (1995)
To facilitate discrimination between the closely related enteropathogens Campylobacter jejuni and C. coli, unique differences in antigenic surface structure were examined. A genomic library of C. jejuni 81116 was constructed in plasmid pBluescriptIISK- and expressed in Escherichia coli K-12. Rabbit hyperimmune serum raised against C. jejuni ATCC 29428 recognized a clone expressing a C. jejuni 24-kDa membrane-associated protein. Antiserum raised against sonicated recombinant E. coli expressing the 24-kDa protein reacted with C. jejuni, whereas C. coli did not react specifically. Determination of the nucleotide sequence of the DNA insert of this recombinant plasmid revealed an open reading frame encoding 214 amino acids; the gene was designated mapA; and its gene product was designated MAPA. The 18 N-terminal amino acid residues constitute a signal sequence characteristic of prokaryotic membrane lipoproteins. In a dot blot hybridization assay with a mapA probe, 120 clinical isolates of C. jejuni were unequivocally discriminated from 126 other campylobacters, including 34 C. coli isolates. A PCR test based on the mapA sequence was developed for identification of C. jejuni. A PCR product was obtained with all of the clinical isolates of C. jejuni tested from human, dog, cat, bovine calf, and chicken sources. Recombinant MAPA with an added C-terminal six-histidine tail was affinity purified and used to immunize rabbits. The rabbit anti-MAPA serum specifically recognized the protein in whole cells of C. jejuni on Western blots (immunoblots). The MAPA protein was present in all of the C. jejuni strains tested and was absent in C. coli and related campylobacters.